Labor share and growth in the long run - Matthieu Charpe; Slim Bridji; Peter McAdam (European Central Bank (ECB), 2019)
This paper establishes some stylized facts of the long run relationship between growth and labor shares using historical data for the United States (1898-2010), the United Kingdom (1856-2010), and France (1896-2010). Performing individual country time-frequency analysis, we demonstrate the existence of long-term cycles in labor share of thirty to fifty years explaining a major part of the variance in the data. Further, the impact of labor share on growth changes sign with the frequency considered from negative at high frequencies to positive at low frequencies. Finally, the positive coefficient associated with the labor share at low frequencies increases
Keywords: E24; E25; N1; 330; Labor share; growth; income distribution; wavelet analysis